2006
DOI: 10.1161/01.res.0000250607.34498.b4
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of Connexins 40 and 43 to Atrial Impulse Propagation in Synthetic Strands of Neonatal and Fetal Murine Cardiomyocytes

Abstract: Abstract-Atrial tissue expresses both connexin 40 (Cx40) and 43 (Cx43) proteins. To assess the relative roles of Cx40 and Cx43 in atrial electrical propagation, we synthesized cultured strands of atrial myocytes derived from mice with genetic deficiency in Cx40 or Cx43 expression and measured propagation velocity (PV) by high-resolution optical mapping of voltage-sensitive dye fluorescence. The amount of Cx40 and/or Cx43 in gap junctions was measured by immunohistochemistry and total or sarcolemmal Cx43 or Cx4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 58 publications
6
88
0
Order By: Relevance
“…In an earlier study, we engineered strands from murine atrial tissue using photomicrolithography to show that linear propagation velocity at a cellular level was markedly decreased with Cx43 ablation and signifi cantly increased versus WT with Cx40 ablation (Beauchamp et al, 2006). These fi ndings were in seeming confl ict with some of the aforementioned studies in whole mice, but in accordance with studies in human hearts.…”
Section: Genetic Deletion Of Connexin In Engineered Atrial Cell Pairssupporting
confidence: 66%
See 2 more Smart Citations
“…In an earlier study, we engineered strands from murine atrial tissue using photomicrolithography to show that linear propagation velocity at a cellular level was markedly decreased with Cx43 ablation and signifi cantly increased versus WT with Cx40 ablation (Beauchamp et al, 2006). These fi ndings were in seeming confl ict with some of the aforementioned studies in whole mice, but in accordance with studies in human hearts.…”
Section: Genetic Deletion Of Connexin In Engineered Atrial Cell Pairssupporting
confidence: 66%
“…This complexity might have several components: There could be interaction (1) between the atrial connexins at the level of expression at the ID, (2) at the level of gap junction channels with formation of heteromeric hemichannels (or connexons) and mixed gap junctions channels composed of all three atrial Cx subspecies, and (3) between connexins and expression of other functional complexes, such as ion channels. Thus, in our earlier work, we could show that the area occupied by Cx40 at the ID decreased with Cx43 ablation, whereas the Cx43 immunofl uorescence signal increased with Cx40 ablation (Beauchamp et al, 2006). These changes occurred with a constant cellular pool of Cx40 and Cx43 proteins, as demonstrated by whole cell Western blots, suggesting the possibility of interaction at the level of traffi cking.…”
Section: Genetic Deletion Of Connexin In Engineered Atrial Cell Pairsmentioning
confidence: 58%
See 1 more Smart Citation
“…In this setting, alterations of cardiac connexins may be looked up as an important mechanism underlying the onset and/or the maintenance of the arrhythmia. Beauchamp et al (2006) demonstrated that connexins Cx40 and Cx43 play a key role in the propagation of atrial impulse. Some studies on human atrial samples of patients with chronic AF reported redistribution of Cx43 and Cx40 labeling towards the lateral borders of atrial myocytes and decreased levels of Cx43 per myocyte in both right atrial appendage and lateral Quantitative densitometric analysis of Cx43 protein at different time points (0, 24, 48 h of hypoxia).…”
Section: Electrical Remodeling Cardiac Connexins and Atrial Fibrillamentioning
confidence: 99%
“…While regulation of ventricular connexin has been investigated in several in vitro models, atrial connexin have been poorly investigated (Beauchamp et al 2006). In this study, we evaluated connexin expression and distribution in atrial cardiomyocytes (HL-1 cells) and the effects of hypoxia/reoxygenation, ischemia in association with normoxia and hypoxia, pro-inflammatory stimuli, neurotransmitters and angiotensin II (Ang II) on Cx43 and Cx40 in the same cells.…”
Section: Aim Of the Studymentioning
confidence: 99%